Optimalisasi Penggunaan Aplikasi Google Maps Sebagai Media Promosi UMKM Bina Sejahtera Bersama Banjarnegara - Solekan, Muhamad; Nuramanah Kinding, Dwi Putriana; Sarno (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2024)
"Bina Sejahtera Bersama" is one of the Micro, Small, and Medium Enterprises (MSMEs) groups located in Banjarnegara Regency, facing challenges in the promotion sector, which consequently affects the development of these MSMEs. Typically, the group's promotions are still reliant on word of mouth and placing their products in local kiosks. This journal discusses the optimization of using the Google Maps application as a promotional medium for the participants of "Bina Sejahtera Bersama" MSME group in Banjarnegara Regency. The methods employed in this community service journal are educational and community assistance methods, accompanied by tests to measure the extent of understanding among the MSME participants. This approach is implemented through direct, comprehensive, and structured information delivery to the Micro, Small, and Medium Enterprises (MSMEs) participants of "Bina Sejahtera Bersama" (BSB) in Banjarnegara Regency regarding the utilization of Google Maps as a promotional medium. Based on pre-tests and post-tests results, there is a 47.5% increase in knowledge. Therefore, it can be concluded that the socialization, training, and assistance activities for using Google Maps as a promotional tool have been successful. These results illustrate the effectiveness of the planned activities, where participants have successfully improved their understanding of the application. This significant improvement indicates that the methods used in the socialization and assistance activities can have a positive impact, supporting participants in better understanding and optimizing the use of Google Maps in promoting their businesses.